NILAI PERSAHABATAN DALAM FILM YOWIS BEN 2 - Novansyah, Rendhy; hakim, lukman (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2023)
Friends are peers who participate in joint activities, support each other and share closeness. Stories are often the main plot in a film's storyline. The Yowis Ben film, which has a duration of 1 hour 49 minutes, is based on the Indonesian comedy-drama genre by Fajar Nugros and Bayu Skak, describing the journey of a local band based on the Javanese language in spreading their band name to the national realm. The purpose of this study is to find out how the views of the characters in the movie